Türkçe Öğretmeni Adaylarının "Hızlı Okuma” Becerisine Yönelik Metafor Algıları - Kemiksiz, Ömer (Muş Alparslan Üniversitesi, 2019)
This study aims to determine the perceptions of pre-service Turkishlanguage teachers towards their speed reading skills through metaphors. Thestudy was carried out with 176 pre-service teachers at Bartın University, Faculty of Education, Department of Turkish Language Education in Fall semesterof 2017-2018 academic year. Of the qualitative research designs, phenomenologywas used in the study and the data were collected through the forms prepared bythe researcher. In the process of data collection, the pre-service teacherswere asked to fill the gaps in phrases such as "Speed reading is like..........., because ……….." The obtained data were analyzed with contentanalysis. At the end of the analysis of the data, it was found that thepre-service Turkish language teachers produced a total of 161 valid metaphors, 122 of which were different. According to the analysis made by taking intoaccount the justification of these metaphors, 10 conceptual categories wereformed for the metaphors produced by the participants.

Bu araştırmanın amacı, Türkçe öğretmeni adaylarınınhızlı okuma becerisine yönelik algılarını metaforlar yoluyla tespit etmektir.Çalışma 2017-2018 eğitim öğretim yılı güz döneminde Bartın Üniversitesi EğitimFakültesi Türkçe Eğitimi Ana Bilim Dalında öğrenim gören 176 öğretmen adayı ilegerçekleştirilmiştir. Nitel araştırma desenlerinden olgu bilimin kullanıldığıaraştırmanın verileri, araştırmacı tarafından oluşturulan formlarlatoplanmıştır. Veri toplama sürecinde öğretmen adaylarından bu formlarda yazılıolan “Hızlı okuma ………. gibidir, çünkü ……….” ifadesindeki boşluklarıdoldurmaları istenmiştir. Elde edilen veriler, içerik analizi ileçözümlenmiştir. Verilerin analizi neticesinde Türkçe öğretmeni adaylarınınhızlı okuma becerisine yönelik 122 farklı olmak üzere toplam 161 adet geçerlimetafor ürettikleri ortaya çıkmıştır. Elde edilen bu metaforların gerekçelendirmeyönleri dikkate alınarak yapılan analizler sonucu, öğretmen adaylarınınoluşturdukları metaforlar 10 kavramsal kategori altında toplanmıştır.
Metaphor Perceptions of Pre-Service Turkish Language Teachers towards "Speed Reading" Skills
anemon
Keywords: Reading Skill; Speed Reading; Metaphor; Perception; Teacher Candidates; Okuma becerisi; hızlı okuma; metafor; algı